Effective leadership in Mexico: an extension of the LEAD project - Michaud, James; Lituchy, Terri R.; Acosta, Mónica; Villegas Romero, Fabiola; Velez Torres, Francisco; Díaz-Gómez, Eduardo Raúl (My University, 2019)
This study examines the applicability of pre-existing effective leadership constructs in Mexico; as well as the commonalities and differences that native Mexicans, and Haitian immigrants, in Mexico have on perceptions of effective leadership. A survey containing both Western and African developed effective leadership measures was administered to both samples. There were significant differences between the samples regarding which leadership factors they perceived to be the most effective. Shared perceived effective factors included being an “effective communicator” and “knowledgeable”. Divergences included Ubuntu leadership which was rejected by Mexicans but approved of by Haitians. Practical recommendations for leading in Mexico are presented.
Journal of African Business
Keywords: Effective leadership; African diaspora; Cross-cultural; México; Haiti; LEAD; Transcultural; Diáspora africana; Campus Mexicali